2003
DOI: 10.1074/jbc.m307052200
|View full text |Cite
|
Sign up to set email alerts
|

Novel Role of 3-Phosphoglycerate Kinase, a Glycolytic Enzyme, in the Activation of L-Nucleoside Analogs, a New Class of Anticancer and Antiviral Agents

Abstract: L-Nucleoside analogs are a new class of clinically active antiviral and anticancer agents. The phosphorylation of these analogs from diphosphate to triphosphate metabolites is crucial for their biological action. We studied the role of 3-phosphoglycerate kinase, a glycolytic enzyme, in the metabolism of L-nucleoside analogs, using small interfering RNAs to down-regulate the amount of this enzyme in HelaS3 and 2.2.15 cells, chosen as models for studying the impact of the enzyme on the anticancer and antihepatit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
32
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 33 publications
(21 reference statements)
0
32
0
Order By: Relevance
“…Although the mono-, di-and triphosphate forms of troxacitabine accumulate in cells, it is interesting that the diphosphate form predominates (Grove et al, 1995). This is likely because of the less efficient phosphorylation of troxacitabine diphosphate to the active metabolite, troxacitabine triphosphate, by 3-phosphoglycerate kinase rather than by nucleoside diphosphate kinase (Krishnan et al, 2002(Krishnan et al, , 2003. Deficiencies in nucleoside transporters do not cause increases in drug resistance, suggesting that cellular uptake of troxacitabine is mainly by passive diffusion (Grove and Cheng, 1996;Gourdeau et al, 2001b).…”
Section: Targeting Dna Replicationmentioning
confidence: 99%
“…Although the mono-, di-and triphosphate forms of troxacitabine accumulate in cells, it is interesting that the diphosphate form predominates (Grove et al, 1995). This is likely because of the less efficient phosphorylation of troxacitabine diphosphate to the active metabolite, troxacitabine triphosphate, by 3-phosphoglycerate kinase rather than by nucleoside diphosphate kinase (Krishnan et al, 2002(Krishnan et al, , 2003. Deficiencies in nucleoside transporters do not cause increases in drug resistance, suggesting that cellular uptake of troxacitabine is mainly by passive diffusion (Grove and Cheng, 1996;Gourdeau et al, 2001b).…”
Section: Targeting Dna Replicationmentioning
confidence: 99%
“…The metabolism of the radiolabeled compounds was monitored according to previously established procedures (17). Briefly, CEM cells were seeded at 10 6 cells/ml and were incubated with 2 M (75 mCi/mmol) of various radiolabeled compounds.…”
Section: Methodsmentioning
confidence: 99%
“…Among them, nm23-H1 and nm23-H2, the predominant isoforms residing in the cytoplasm (18), have been characterized in detail with regard to their kinetic properties and catalytic mechanisms (29). Other enzymes that are able to phosphorylate nucleoside diphosphates include creatine kinase (CK), pyruvate kinase (PK), and 3-phosphoglycerate kinase (PGK) (14)(15)(16)(17). Our previous studies demonstrated that TK1 is the enzyme responsible for the phosphorylation of 4Ј-ethynyl D4T to 4Ј-ethynyl D4TMP (6).…”
mentioning
confidence: 99%
“…In addition to its metabolic role, the phosphoryl transfer activity of PGK is important in the processing of antiretroviral prodrugs that take the form of L-nucleoside analogues (2). The rate-limiting step in the in vivo activation of such compounds has been demonstrated to be the addition of a third phosphate by PGK (3). A third activity of PGK is as a signaling molecule in chordates.…”
mentioning
confidence: 99%